Al-Farabi on acquiring a philosophical concept. - Khalidi, Muhammad Ali (British Journal for the History of Philosophy, 2024)
This paper focuses on a discussion in Abu Nasr al-Farabi's Book of Letters (Kitāb al-Ḥurūf), which has to do with the importation of philosophical (including scientific) discourse from one language or nation (ummah) to another. The question of importing philosophical discourse from one language or nation to another touches on Farabi's views on a number of important philosophical questions. It reveals something about his views on the nature of philosophical and scientific concepts and their relation to concepts in non-philosophical or 'popular' discourse, as well as the means of grasping previously unencountered concepts. In this article, I will discuss these issues both to ascertain Farabi's views as well as to shed some light on them in their own right. I will argue that Farabi thinks that the understanding of some novel philosophical or scientific concepts sometimes depends on the grasp of related concepts from ordinary discourse, and that experts rely on these everyday concepts in acquiring the more specialized concepts. If the same linguistic terms are used to denote both concepts, they will be ambiguous, but this can be considered a case of 'productive ambiguity,' since it aids in the acquisition of novel concepts.